ASSESSMENT OF COMPLICATIONS USING DIFFERENT METHODS AFTER TONSILLECTOMY - Qussy Khashan Majid Almajid; Qaysar Abdulwahhab Suker Alseaeadey; Majid Jalil Radhi (Scholar Express Journals, 2022)
This study focuses to assess and compare for patients who have had tonsillectomy, depending on different techniques in the severity of pain. 40 patients were collected from different Hospitals, Thi-Qar, Iraq, and the patients were distributed to the methods used for tonsillectomy, which are plasma blade 20 patients and bipolar radiofrequency clamp 20 patients This study was divided into two groups, BRC and PB, for the purpose of tonsillectomy. The average age of patients, in general, ranged between 10 and 31 years, and the evaluation was done by reading the severity of the pain in relation to the first day, the second and sixth days, and We conclude PB is the best method, which is preferred to be used.
Keywords: BRC; PB; compare; pain